The effect of sport education on empowerment and self-confidence - Sukiri, Sukiri; Widyawan, Dena; Setiawan, Iwan; Pelana, Ramdan; Sari, Eka Fitri Novita; Razali, Razali (Jurnal Cakrawala Pendidikan, 2024)
This study aims to examine the effect of the application of two different learning models (Sport Education and Traditional Teaching) by pre-service teachers on the empowerment and self-confidence of students in physical education classes at secondary schools. The research design used was a quasi-experimental pretest-posttest. The research sample was 429 high school students involving 8 schools in Jakarta, Indonesia. The sample consisted of 220 girls and 209 boys aged between 15 to 18 years old. The instruments used were the Psychological Empowerment Instrument and the Competitive State Anxiety Inventory-2 (CSAI-2). The results show that the Sport Education learning model can significantly increase student’s self-confidence and empowerment, while in the Traditional Teaching model student’s self-confidence and empowerment did not have a significant increase. The results of this study prove that the Sport Education model is better than the Traditional Teaching model.